The options in remote phosphor structure for better white LEDs color quality - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2020)
The WLEDs configuration with remote phosphor layers has higher luminescent performance than WLEDs with dispense coating or conformal coating and is applied for many modern devices. However, managing the chromatic performance of lighting structure with remote phosphor materials is a challenging objective that demands more research. This has inspired the usage of multi phosphor configurations with distance in between the layers to improve color quality. The results of this manuscript can support the manufacturers in choosing the optimal configuration for optical performance in LEDs devices with more than one phosphor material. The simulated model used in the experments is 6500 K CCT WLEDs, which results show the triple-layers structure is more favorable in terms of color quality and light output. Besides, a notable reduction occurs in color deviation means that chromatic stability is also enhanced in WLEDs with three phosphor layers. Through experimental results, which were confirmed by the Mie-scattering theory, this research offers valuable approach and details to produce better WLEDs.